Boards in microfinance institutions: how do stakeholders matter? - Neema Mori; Roy Mersland (Journal of Management & Governance, 2014)
Microfinance Institutions provide financial services to poor people. Governance of these organizations is important so that they can operate efficiently and sustainably. This study analyzes the influence of stakeholders (donors, employees, customers, and creditors), on board structure (board size and CEO duality), and on organizational performance. We use a global data set of 379 microfinance institutions from 73 countries, collected from rating organizations. Supported by stakeholder theory, agency theory and resource dependence theory, we find stakeholders to be important and have various influences on microfinance institutions. We find donors to be associated with small boards, non-duality and better performance. Employees are associated with large boards, while customers are associated with duality and good financial performance. Creditors opt for duality and better social performance. Implications and areas for future research are discussed.
Keywords: 650